2013
DOI: 10.3390/molecules18055761
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Infective Potential of Marine Invertebrates and Seaweeds from the Brazilian Coast

Abstract: This manuscript describes the evaluation of anti-infective potential in vitro of organic extracts from nine sponges, one ascidian, two octocorals, one bryozoan, and 27 seaweed species collected along the Brazilian coast. Antimicrobial activity was tested against Staphylococcus aureus (ATCC 25923), Enterococcus faecalis (ATCC 29212), Pseudomonas aeruginosa (ATCC 27853), Escherichia coli (ATCC 25922) and Candida albicans (ATCC 10231) by the disk diffusion method. Antiprotozoal activity was evaluated against Leis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 46 publications
(53 reference statements)
0
27
0
Order By: Relevance
“…Moreover, when manzamine A was chemically transformed to its salt forms, the anti-HSV-1 activity was improved suggesting that augmentation of the overall water solubility can significantly enhance the activity (Jayavardhana et al, 2017). In view of these data and also considering the previous published work of our group (Bianco et al, 2013) that showed the anti-herpes activity of the buthanolic extract of Haliclona sp. collected in Aranhas Island, Santa Catarina State, South Brazil, species of this genus should receive special attention for future works aiming the isolation and structural elucidation of their bioactive metabolites.…”
Section: Speciesmentioning
confidence: 58%
“…Moreover, when manzamine A was chemically transformed to its salt forms, the anti-HSV-1 activity was improved suggesting that augmentation of the overall water solubility can significantly enhance the activity (Jayavardhana et al, 2017). In view of these data and also considering the previous published work of our group (Bianco et al, 2013) that showed the anti-herpes activity of the buthanolic extract of Haliclona sp. collected in Aranhas Island, Santa Catarina State, South Brazil, species of this genus should receive special attention for future works aiming the isolation and structural elucidation of their bioactive metabolites.…”
Section: Speciesmentioning
confidence: 58%
“…(SI of 7.5) were effective against L. brasiliensis amastigotes (IC 50 = 24 and 40 μg/ml, respectively), and C. cervicornis, C. cupressoides, Dictyota sp. and O. secundiramea were strongly cytotoxic for bone marrow macrophages (Bianco et al, 2013). Nara et al (2005) explored the inhibition potential of extracts from brown, red and green marine algae against the recombinant T. cruzi dihydroorotate dehydrogenase (DHOD), an essential enzyme involved in pyrimidine biosynthesis.…”
Section: Algae Drugs Against Ntdmentioning
confidence: 99%
“…The extracts did not show activity against T. cruzi (VonthronSénécheau et al, 2011). Bianco et al (2013) evaluated the antiprotozoal activity of 27 algae species against L. braziliensis promastigotes and intracellular amastigotes and against T. cruzi epimastigotes/ intracellular amastigotes. Six of the 27 species assayed showed activity against these protozoa.…”
Section: Algae Drugs Against Ntdmentioning
confidence: 99%
“…Previous studies have focused on the discovery of chemical compounds with pharmaceutical or ecological potential in Laurencia complex (Blunt et al, 2011). In spite of the reports regarding antibacterial, antiviral and cytotoxic activities (Machado et al, 2010), there are only four studies on the antileishmanial action of Laurencia crude extracts (Freile-Pelegrin et al, 2008;Bianco et al, 2013) and their sesquiterpenes (Santos et al, 2010;Machado et al, 2011). Only few reports have addressed inter or intraspecific variation in secondary metabolite composition and none of them have considered the impact of chemical variability on bioactivity (Yuan et al, 2009;Stengel et al, 2011;Sudatti et al, 2011;Oliveira et al, 2013).…”
Section: Introductionmentioning
confidence: 96%